The Impact of Diet and Photoperiodism on the Life History of Thanatophilus sinuatus (Coleoptera: Silphidae) - Qubaiová, J; Jakubec, P; Montoya-Molina, S; Novák, M; Šuláková, H (Journal of medical entomology, 2023)
The forensically important genus Thanatophilus Leach, 1815 (Coleoptera: Silphidae) is a widespread group of carrion beetles that occupies the Holarctic and Afrotropical realms. It has recently received more recognition, as its species are frequently detected on large carrion, including humans, and can be useful in estimating the time of colonization (TOC) and the post-mortem interval (PMI). The immature stages of Thanatophilus sinuatus (Fabricius, 1775) were reared on three different meat diets (pork liver, pork muscle, and chicken muscle). Diet influence on some of the essential life history traits of the species was examined for different populations. Our findings indicated an accelerated development on pork muscle followed closely by pork liver and a prolonged development on chicken muscle. The diet significantly affected the size, and the body condition (weight/ size) as both pork muscle and liver produced individuals in better physical condition (larger and heavier). The impact of two cyclic photoperiod regimes (16 h Light (L): 8 h Dark (D) and 12 h L: 12 h D) was further evaluated and indicated no significant variability.
Keywords: brouci; necrophagous; photoperiod; Feeding Behavior; rozmnožování; development time; Diet; dieta; Reproduction; zvířata; Humans; survival; Coleoptera; stravovací zvyklosti; lidé; nutritional ecology; Animals